2018
DOI: 10.1111/desc.12695
|View full text |Cite
|
Sign up to set email alerts
|

Explaining early moral hypocrisy: Numerical cognition promotes equal sharing behavior in preschool‐aged children

Abstract: Recent work has documented that despite preschool-aged children's understanding of social norms surrounding sharing, they fail to share their resources equally in many contexts. Here we explored two hypotheses for this failure: an insufficient motivation hypothesis and an insufficient cognitive resources hypothesis. With respect to the latter, we specifically explored whether children's numerical cognition-their understanding of the cardinal principle-might underpin their abilities to share equally. In Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 63 publications
8
32
0
Order By: Relevance
“…If yes, such results would tend to cast doubt on the first and second possibilities listed above and to support the third possibility instead. Such results would also dovetail well with recent findings that preschoolers sometimes perform poorly in first- and third-party fairness tasks due to cognitive limitations in their ability to encode and remember exact numerical information (e.g., Chernyak et al, 2016, 2019; Chernyak and Blake, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…If yes, such results would tend to cast doubt on the first and second possibilities listed above and to support the third possibility instead. Such results would also dovetail well with recent findings that preschoolers sometimes perform poorly in first- and third-party fairness tasks due to cognitive limitations in their ability to encode and remember exact numerical information (e.g., Chernyak et al, 2016, 2019; Chernyak and Blake, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Many children in our study allocated tokens one at a time to each box, suggesting a strategy of matching tokens to boxes or animals via one-to-one correspondence. Furthermore, even before preschoolers can count, they understand norms of equal sharing and are able to use turn-taking strategies, demonstrate awareness of the equality norm for dividing resources, and fairly distribute resources (e.g., Chernyak, Harris, & Cordes, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This particular finding underscores the importance of going beyond studying age-related changes and studying the cognitive predictors and underpinnings of why those age-related changes occur. Recent work has taken an interest in understanding the cognitive underpinnings of prosocial behavior ( Blake et al, 2015b ; Cowell et al, 2017 ; Steinbeis and Over, 2017 ; Chernyak et al, 2018 ). Our study adds to this work by highlighting that general cognitive ability explains a substantial portion of the variance in prosocial behavior, underscoring the importance that various domain-general abilities may serve as important pre-requisites for our prosocial tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, research on children’s prosociality has identified three primary forms that emerge before or by 3 years of age: instrumental helping (i.e., helping others achieve a goal; Warneken and Tomasello, 2006 ), comforting (i.e., sympathizing and offering help to those in distress; Svetlova et al, 2010 ; Dunfield, 2014 ), and costly resource sharing ( Blake and Rand, 2010 ; Chernyak and Kushnir, 2013 ; Chernyak et al, 2017 , 2018 ). Although these behaviors appear in a range of societies, all three forms have not been tested in single non-Western society.…”
Section: Introductionmentioning
confidence: 99%